School improvement and peer learning partnerships: building organizational resilience in primary schools in England - Godfrey, David; Munoz-Chereau, Bernardita (Frontiers in Education, 2024)
Introduction This article looks at organizational resilience (OR) through the analysis of a sub-set of data gained from an independent and embedded mixed methods implementation and process evaluation (IPE) of the Schools Partnership Program (SPP) implemented over 3 years (2018–2021) and funded by the Education Endowment Foundation (EEF) in England. We describe ways in which SPP ‘learning map’ addresses the (i) anticipation, (ii) coping and (iii) adaptation stages and the extent to which SPP helped building organizational resilience. Taking this theoretical framework as a foundation is a novelty, as despite OR has become prominent in the academic literature apart from a few exceptions there is a dearth of international research examining OR within the school sector. Methods A sample of 422 primary schools that took part in SPP (treatment schools) and their comparisons are analyzed applying the organizational capability-based framework. Drawing on SPP empirical data from numerous data collection strategies (interviews, surveys, shadowing school reviews and improvement workshops), the extent to which schools’ resilience capacities were improved is analyzed. Results Our findings suggest that SPP supported the development of OR in SPP primary schools. Despite facing several challenging external factors (student deprivation, the COVID disruption, changes to the external accountability framework and competing demands of other partner organizations) and internal factors (teacher attrition, need to developing leaders, upgrade pedagogical skills and encourage student subgroups who were underperforming) SPP schools exert (1) knowledge building through training, the review process, professional dialogue, learning from each other, as well as receiving and giving feedback. Regarding (2) resource availability, schools used SPP as a scaffold to build improvised strategies to access and mobilize shared human and physical resources; (3) social resources were built in the SPP through social capital, sharing of knowledge, enhancing a shared vision and trust. Finally, (4) SPP promoted lateral power dynamics driven by professional learning and accountability. Discussion Overall, the paper extends the understanding of school peer review approaches for school improvement and adds to the OR international literature by presenting features that extend it toward building system resilience.